PENGOPERASIAN WATER TREATMENT PLANT DI PT PJB UNIT PEMBANGKITAN PAITON - Nurmiati Pasra; Faisol Hakim (Energi & Kelistrikan, 2015)
Water is the main products and basic necessities in the process of generating electrical energy in a steam power plant. Several processes are needed to produce water with permitted conductivity and PH. Steam Power Plant Paiton 2 x 400 MW has two water treatment plant unit with demineraleralized water products flow 2 x 108 m³/ jam. Filling process of steam power plant is started by charging Hotwell condensor of Condensate Storage Tank (CST). By using condensate pump, water is pumped into the Deaerator, then fill the drum with pump Boiler Feed Pump (BFP). In the drum, separation of water and vapor phase will occur. Pressurized wet steam is heated using steam superheater to produce dry steam and supplied to the turbine by settings via Main Stop Valve. Because the generator and turbine are in the same axis, generator is now able to produce electricity. There will be excess water in the Condensate Storage Tank in charging state due. Manual operation which can waste demineraleralized water which furthermore can cause losses and decrease efficiency in the operation system. With the addition of the level sensor in the Condensate Storage Tank, overflowing water in demineraleralized water filling the tank can be avoided.